Uji efek antibiofilm ekstrak siwak (salvadora persica) Terhadap aggregatibacter actinomycetemcomitans - Sundjojo, Mikha; Haura Khaerunnisa, Athaya (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: The health problem complained by Indonesian people is periondontitis caused by biofilm. A.actinomycetemcomitans biofilm showed higher resistance to antibiotic than planktonic cells, so research was developed on the use of an effective and safe natural ingredient, namely the siwak plant (Salvadora persica). Aim: To determine the effectiveness of siwak (Salvadora persica) extract on A.actinomycetemcomitans biofilm density. Methods: This research is a laboratory experimental study using the biofilm test method. Siwak extract were taken from Balitro in Bogor, West Java. This research was conducted at the FKG Usakti MiCore Laboratory. The siwak (Salvadora persica) extract was diluted to obtain concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.12% and 1.5%. Results: The normality test results using the Shapiro-Wilk method at the incubation period of 1 hour, 3 hours and 24 hours showed that the data were normally distributed (p>0.05). The results of the one-way ANOVA test for the three incubation periods showed significantly different data (p<0.05) with a p=0.000. The results of the LSD Post-Hoc test showed differences in significance at each concentration at each incubation period. Conclusion: There is an effect of siwak extract (Salvadora persica) with the highest inhibition on A.actinomycetemcomitans biofilm density at a concentration of 25%.